Asiatic Acid Inhibits Nasopharyngeal Carcinoma Cell Viability and Migration via Suppressing STAT3 and Claudin-1 - Supitchaya Pantia; Thaned Kangsamaksin; Tavan Janvilisri; Waraporn Komyod (MDPI AG, 2023)
Nasopharyngeal carcinoma (NPC) is a prevalent cancer in Southeast Asia, but effective treatment options remain limited, and chemotherapy has a high resistance rate. Asiatic acid (AA), a triterpenoid found in Centella asiatica, has shown anticancer activity in various cancers. Therefore, this study aims to investigate the anticancer effects and mechanisms of AA in NPC cell lines. The effects of AA on NPC cytotoxicity, apoptosis, and migration were determined in TW-01 and SUNE5-8F NPC cell lines. Western blot analysis was performed to evaluate the protein expression levels affected by AA. The role of AA in proliferation and migration was investigated in STAT3 and claudin-1 knockdown cells. AA inhibited NPC cell viability and migration and induced cell death by increasing cleaved caspase-3 expression. Moreover, AA inhibited STAT3 phosphorylation and reduced claudin-1 expression in NPC cells. Although knockdown of STAT3 or claudin-1 slightly reduced cell viability, it did not enhance the anti-proliferative effect of AA. However, knockdown of STAT3 or claudin-1 increased the anti-migratory effect of AA in NPC cells. These results suggest that AA can be a promising candidate for drug development against NPC.